Interactive Media Eight Standard Public Service Procedures in Bureaucracy Reform at Indonesian Institute of Arts Denpasar - Putraka, Agus Ngurah Arya; Janottama, I Putu Arya; Putra, Gede Bayu Segara (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2023)
This article is a description of the interactive media design process as a means of socializing the Eight Standards of Public Service Procedures in Bureaucratic Reform at the Indonesian Arts Institute campus in Denpasar in 2021. Digital media has a short access speed, which is the advantage of visual communication media that are designed to be able to interact reciprocally back with the target, namely the publics. The targets of this media can interact through navigation in the media, so that the public will more easily obtain information about the eight public service standards in bureaucratic reform that have been implemented at the Indonesian Art Institute, Denpasar. Through this latest media, it is hoped that the public will find it easier to access and find information about the eight standards, to create an interactive media that functions optimally in conveying information on the eight lane standard of public service procedures, so in designing this interactive media the author will use a qualitative descriptive method so that the results can be justified. This interactive media about eight standard public service procedures in bureaucratic reform was created by the author along with 2 members and involved 2 students who will be worked on for 1 year by going through several stages of creation, namely the data collection process, then designing storyboards, and visual design and digitization processes using a design program that supports, and the final process of this interactive media is to test the community's response to the application that has been created. It is hoped that this interactive application will be able to assist stakeholders in implementing policies in bureaucratic reform within the Indonesian Institute of the Arts Denpasar.